MANAGEMENT PRACTICES FOR ENHANCING FERTILIZER USE EFFICIENCY UNDER RICE-WHEAT CROPPING SYSTEM IN THE INDO-GANGETIC PLAINS - Sarkar, Sukamal (Innovare Journal of Agricultural Sciences, 2015)
Rice and wheat are the staple foods for almost the entire Asian population and therefore they occupy a premium position among all food commodities. The era of the Green Revolution started during the early 1970s with wheat and rice and since then the rice-wheat cropping system of the Indo-Gangetic Plains has played a significant role in the food security of the region. However, recent years have witnessed a significant slowdown in the yield growth rate of this system and the sustainability of this important cropping system is at risk due to second-generation technology problems and mounting pressure on natural resources. Traditional cultivars and conventional agronomic practices are no longer able to even maintain the gains in productivity achieved during the past few decades. Demand for food is increasing with the increasing population and purchasing power of consumers. The rice-wheat cropping system is labour-water-and energy-intensive and it becomes less profitable as these resources become increasingly scarce and the problem is aggravated with deterioration of soil health, the emergence of new weeds, and emerging challenges of climate change. Therefore, a paradigm shift is required for enhancing the system's productivity and sustainability. The 4R Principles of applying right source of nutrients, at the right rate, at the right time and at the right place is expected to increase nutrient use efficiency, productivity and farm profit in rice-wheat cropping system production and provides opportunity for better environmental stewardship of nutrients. Â Keywords: Best Management Practices, Cropping system, Indo-Gangetic Plains, Sustainability.